Hak Asasi Manusia dalam Perspektif Barat dan Islam - Triana, Nita (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Universal Declaration of Human Rights (UDHR) 1984 is a moral document that realizes the principles of United Nation charter as a measurement standard which is admitted for identifying rights and many kinds of freedom. In Islam's point in view, human rights have been explained since 14 centuries ago in Madinah charter and in Al Qur’an as well. Human rights in both western and Islam perspective admit individual rights which are legally guaranteed by the nation. However, there are differences and those are explained in the Cairo Declaration of Human Rights in Islam (CDHRI).